1995
DOI: 10.1084/jem.182.5.1291
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis-inducing epitope of myosin binds constitutively and stably to I-Ak on antigen-presenting cells in the heart.

Abstract: SummaryImmune interactions in the heart were studied using a murine model of myosin-induced autoimmune myocarditis. A T cell hybridoma specific for mouse cardiac myosin was generated from A/J mice and used to demonstrate that endogenous myosin/I-A k complexes are constitutively expressed on antigen-presenting cells in the heart. This T cell hybridoma, Seu.5, was used as a functional probe to identify a myocarditis-inducing epitope of cardiac myosin. Overlapping peptides based on the cardiac myosin heavy chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
122
2
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 40 publications
1
122
2
3
Order By: Relevance
“…Cardiac-resident macrophages exhibiting an M2-like gene expression profile were found to be distributed in close association with the coronary vascular bed (3), and niches for dendritic cells (CD11c + MHC-II high CD80/86 low ) were found near the cardiac valves of the intact heart (1). It was also demonstrated that cardiac-resident MHCII + cells process and present myosin heavy chain-alpha-derived peptides under steady-state conditions (11,12) and prime T cells ex vivo (1). However, whether lymphocytes can seed the intact myocardium and whether T-cell priming with myocardial antigens can occur in the absence of an infection or autoimmune myocarditis remain elusive.…”
mentioning
confidence: 86%
“…Cardiac-resident macrophages exhibiting an M2-like gene expression profile were found to be distributed in close association with the coronary vascular bed (3), and niches for dendritic cells (CD11c + MHC-II high CD80/86 low ) were found near the cardiac valves of the intact heart (1). It was also demonstrated that cardiac-resident MHCII + cells process and present myosin heavy chain-alpha-derived peptides under steady-state conditions (11,12) and prime T cells ex vivo (1). However, whether lymphocytes can seed the intact myocardium and whether T-cell priming with myocardial antigens can occur in the absence of an infection or autoimmune myocarditis remain elusive.…”
mentioning
confidence: 86%
“…In fact, unique epitopes within cardiac myosin have been described to produce myocarditis. Myocarditis was induced by amino acid residues 334 to 352, located in the S1 region of A/J mouse cardiac myosin, 26 residues 736 to 1032 in BALB/c cardiac myosin, 59 acetylated residues 614 to 643 of rat cardiac myosin produced disease in BALB/c mice, 56 residues 1070 to 1165 of porcine cardiac myosin induced disease in Lewis rats, 57 residues 1107 to 1186 in the Lewis rat, 64 and acetylated Lewis rat LMM region residues 1539 to 1555. 58 Our studies in Lewis rats (Galvin et al, manuscript in preparation) suggest that epitopes within the LMM region produce valvulitis whereas the most severe myocarditis is produced by an epitope within the S2 region of cardiac myosin (Cunningham and Li, unpublished data).…”
Section: Susceptibilty To Myocarditis In Rodent Modelsmentioning
confidence: 99%
“…One such model for cardiac autoimmunity is experimental autoimmune myocarditis (EAM), which involves induction of disease in susceptible rodent strains by immunizing animals with cardiac antigens or their peptide fragments. 23e25 In this study, we used the EAM model in A/J mice to demonstrate that ANT 1 possesses multiple immunodominant epitopes, and one of these, ANT 1 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], was found to induce myocarditis in the immunized animals. Furthermore, myocarditogenicity of ANT 1 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] was associated with the generation of T cells capable of producing predominantly IL-17A, and the antigen-sensitized T cells can transfer the disease to naïve recipients, suggesting that ANT 1 can be a potential autoantigen in the heart autoimmunity.…”
mentioning
confidence: 99%